High strength-ductility nano-structured high manganese steel produced by cryogenic asymmetry-rolling. Issue 4 (April 2018) - Fu, Bin; Fu, Liming; Liu, Shichang; Wang, Huan Rong; Wang, Wei; Shan, Aidang
Abstract: A bulk nanostructured twinning-induced plasticity (TWIP) steel with high ductility and high strength was fabricated by cryogenic asymmetry-rolling (cryo-ASR) and subsequent recovery treatment. It was found that the cryo-ASRed TWIP steels exhibit simultaneous improvements in the ductility, strength and work hardening. Typical microstructures of the cryo-ASR TWIP steel were characterized by shear bands and intensive mechanical nano-sized twins induced by cryogenic deformation. These mechanical nano-scale twins remain thermally stable during the subsequent recovery treatment. It is believed that the ductility enhancement and high work-hardening ability for the cryo-ASR TWIP steels should be mainly attributed to the high-density pre-existing nano-scale twins.